Use of three-dimensional time-resolved phase-contrast magnetic resonance imaging with vastly undersampled isotropic projection reconstruction to assess renal blood flow in a renal cell carcinoma patient treated with sunitinib: a case report - Takayama, Tatsuya (BioMed Central, 2014)
BACKGROUND: New imaging modalities to assess the efficacy of drugs that have molecular targets remain under development. Here, we describe for the first time the use of time-resolved three-dimensional phase-contrast magnetic resonance imaging to monitor changes in blood supply to a tumor during sunitinib treatment in a patient with localized renal cell carcinoma. CASE PRESENTATION: A 43-year-old Japanese woman with a tumor-bearing but functional single kidney presented at our hospital in July 2012. Computed tomography and magnetic resonance imaging revealed a cT1aN0M0 renal cell carcinoma embedded in the upper central region of the left kidney. She was prescribed sunitinib as neoadjuvant therapy for 8 months, and then underwent partial nephrectomy. Tumor monitoring during this time was done using time-resolved three-dimensional phase-contrast magnetic resonance imaging, a recent technique which specifically measures blood flow in the various vessels of the kidney. This imaging allowed visualization of the redistribution of renal blood flow during treatment, and showed that flow to the tumor was decreased and flows to other areas increased. Of note, this change occurred in the absence of any change in tumor size. CONCLUSION: The ability of time-resolved three-dimensional phase-contrast magnetic resonance imaging to provide quantitative information on blood supply to tumors may be useful in monitoring the efficacy of sunitinib treatment.